Analysis of manganese nodules from the Atlantic - A M Ehrlich (PANGAEA, 1968)
Concentrations of the rare earths have been determined in ten modern manganese nodules from the Atlantic, Pacific, and Indian Oceans, the Baltic Sea, and Lake Charlotte in Nova Scotia. A nodule from a Paleozoic era sea in Montana, a manganese film from a coral found on the Mid-Atlantic Ridge, and samples of the manganese and phosphorite pavements fround on the Blake Plateau were also analyzed. The manganese pavement, a mixed manganese-phosphate concretion from the Blake Plateau and one of the Atlantic nodules with its underlying red clay core were segmented and analyzed.
Supplement to: Ehrlich, AM (1968): Rare earth abundances in manganese nodules [dissertation]. Massachusetts Intitute of Technology, Boston, Massachusetts, USA, 222 pp